Pengetahuan Masyarakat tentang 5 Pilar STBM di Desa Ahu Kecamatan Tapalang Barat - Agustina, Agustina; Adiningsih, Ridhayani; Ahmad, Haeranah; Ganing, Abdul (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Mamuju, 2023)
The Government of Indonesia implements the Community-Based Total Sanitation Program (STBM), which is one of the national programs (Central Government and Local Government) to increase rural population access to proper drinking water and sanitation facilities with a community-based approach, The research was conducted to find out how the level of public knowledge regarding the 5 pillars of STBM. The research method used is descriptive method. The research location was conducted in Ahu Village, West Tapalang District with a total population of 409 families and a sample size of 202 families. The data collection technique was carried out by random sampling, namely providing equal opportunities for the population to be selected as the sample in this study. Based on the data from the results of the research conducted, it was shown that the level of public knowledge about pillar 1 of open defecation was 12 people (5.9%) with a good level of knowledge while the level of knowledge was not good as many as 190 people (94.1%). Pillar 2 CTPS as many as 16 people (7.9%) with a good level of knowledge while the level of knowledge is not good as many as 186 people (92.1%). Pillar 3 PMMRT as many as 10 people (5.0%) with a good level of knowledge while the level of knowledge is not good as many as 192 people (95.0%). Pillar 4 PSRT as many as 15 people (7.4%) with a good level of knowledge while the level of knowledge is not good as many as 187 people (92.6%). Pillar 5 PLCRT as many as 8 people (4.0%) with a good level of knowledge while the level of knowledge is not good as many as 194 people (96.0%). school for 55 people. The conclusion of this study is that the community's knowledge of the 5 pillars of STBM is not good. As for the suggestions in this study, it is hoped that the related puskesmas will carry out counseling to increase community knowledge about the 5 pillars of STBM.